At risk - Cornwell, Patricia Daniels (New York : Berkley, 2007)
A Massachusetts district attorney running for governor wants to use some radical new DNA technology to solve a long-ago murder. The result? A new round of violence.
Keywords: Public prosecutors -- Massachusetts -- Fiction; DNA fingerprinting -- Fiction; Criminal investigation -- Fiction; Massachusetts -- Fiction; Tennessee -- Fiction; Mystery fiction